2015
DOI: 10.1039/c5an00947b
|View full text |Cite
|
Sign up to set email alerts
|

Highly sensitive detection of carbon dioxide by a pyrimido[1,2-a]benzimidazole derivative: combining experimental and theoretical studies

Abstract: In the present paper, a "light-up" chemsensor with a high specificity for carbon dioxide detection using a pyrimido[1,2-a]benzimidazole derivative (P1H) in liquid media has been developed. The results show that P1H reacts with carbon dioxide activated by a basic ion to form a carboxylic acid compound (P1-COOH). These results also provide a possible method for carboxylation reactions of P1H using carbon dioxide based on a vinyl carbanion. The complete reaction mechanism cycle was also described using DFT calcul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…Interestingly, few studies have shown that chemo sensor compounds displaying high selectivity for the fluoride anion were able to detect carbon dioxide gas with full restoration of their original colours and spectral properties [ 11 , 12 ]. Xia and co-workers reported the carboxylation of pyrimido [ 1 , 2 ] benzimidazole and squarine derivatives by the aid of carbon dioxide in the presence of an excess of a fluoride salt [Bu 4 N] F [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, few studies have shown that chemo sensor compounds displaying high selectivity for the fluoride anion were able to detect carbon dioxide gas with full restoration of their original colours and spectral properties [ 11 , 12 ]. Xia and co-workers reported the carboxylation of pyrimido [ 1 , 2 ] benzimidazole and squarine derivatives by the aid of carbon dioxide in the presence of an excess of a fluoride salt [Bu 4 N] F [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%